Cannabidiol enhances cerebral glucose utilization and ameliorates psychopathology and cognition: a case report in a clinically high-risk mental state - Köthe, Dagmar; Rohleder, Cathrin; Kracht, Lutz; Leweke, F. Markus (Frontiers in psychiatry, 2023)
Adolescent individuals often present with subtle, sub-threshold psychiatric syndromes that fluctuate or persist for years. These symptoms have been classified as Clinically High-Risk mental states (CHR), negatively affecting these individuals’ psychosocial development and integration by reducing performance and affecting interpersonal relations. The pathophysiological underpinnings have not been studied in detail, contributing to the current lack of appropriate intervention strategies. This case report sheds new light on potential pathophysiological mechanisms of this condition, which may be addressed by novel treatment approaches such as cannabidiol. A 19-year-old student presented to our early intervention center with a marked cognitive decline within 6 months, anhedonia, ambivalence, social withdrawal, poverty of speech, and brief intermittent psychotic symptoms (delusions and hallucinations). He was diagnosed with CHR state, and we decided to treat him with the non-psychotomimetic phytocannabinoid cannabidiol. Cannabidiol is a promising compound carrying an orphan drug approval for rare certain childhood epilepsy types and is under investigation as an antipsychotic compound with a new mechanism of action compared to existing antipsychotics. We investigated the effect of oral cannabidiol (600  mg per day) over 4 weeks on psychopathology and cerebral glucose utilization. We observed no relevant side effects but a significant clinical improvement. In addition, positron emission tomography (PET) showed a considerable increase in cerebral [18F]fluoro-2-deoxyglucose (FDG) uptake in various brain regions.This finding suggests that cannabidiol may enhance cerebral glucose utilization, possibly via activation of peroxisome proliferator-activated receptor-gamma (PPAR-γ) by its endogenous ligand anandamide or related N-acylethanolamines. This mechanism may represent a new innovative treatment approach for CHR, especially given that many individuals with CHR and early psychosis do not substantially benefit from current psychopharmacological interventions.